Transformation of operational management of machine tools, machine complexes operation with the help of «Operational Management System» - О. P. Korzhova; D. S. Makashin; P. E. Popov; I. E. Donoaga; А. V. Obryvalin (Омский научный вестник)
The article focuses on the potential integration of the SFM digital control system into production. To achieve a more accurate implementation of the dSFM system, the article identifies its strengths and weaknesses. It evaluates and outlines the factors contributing to the successful implementation of the dSFM system in production. The article also analyses the traditional Lean manufacturing system, the analogue SFM system and its digital version. The study scrutinised the manner in which workers interact with the «System of Operations Management» with the purpose of refining its assimilation into manufacturing processes and enhancing employee output.